Efeito da Altura da Coluna na Flotação de Minério Fosfático em Diferentes Granulometrias - Santana, Ricardo Corrêa de (2011)
Since phosphorus (P) deficiency restricts crop yields severely, fertilization with this element phosphorus becomes indispensable to increase agricultural production and consequently, to feed growing world population. Apatite concentrate obtained from phosphate rock beneficiation is used in the manufacture of phosphate fertilizers. Mineral froth flotation is one of the most common and important methods employed to separate and concentrate particles of valuable minerals. Among the various types of flotation equipment, the flotation column has proved to be the most suitable equipment for processing low-grade ores, presenting a high degree of liberation only in a range of fine sizes. One of the main factors that affect flotation performance is the mineral particle size. According to some researchers in a given flotation system (mineral, reagent combinations and flotation machine) there is a narrow range of optimum particle sizes, and that very fine and very large particles achieve a lower flotation performance. Also, fine and coarse particles show different sensitivities to the reagent concentration. Besides chemical and operational factors, the separation by flotation is strongly affect by equipment factors. Thus, the column dimensions as the height are important design variables which directly influences, for example, the residence time of particles and bubbles inside the equipment. This work aimed to investigate the effect of the mineral particle size, the column height and reagent dosages on phosphate ore batch flotation in column. For each granulometric fraction (coarse, intermediate and fine), five column height were evaluated. For this analysis, in each column dimension, two-level full factorial experiments were conducted to study the parameters of collector and gangue depressant dosage. The entire set of experimental data was analyzed globally by multiple regression, measuring the effects of those variables and fitting a model. The response surface analysis allowed for the identification of some combinations of operational conditions yielding higher P2O5 grade and recovery rates than the required values. Furthermore, for fine particles, a study of dissolved air flotation (flotation with microbubble) was performed. In general, on the contrary of the PO grade, the apatite recovery tended to increase with the redution of particle size and depressant dosage and with the increment of collector concentration. A more selective separation was found for coarse particles, taller columns and 25low collector level. For a particle size interval with sieve diameter between 44 and 105 μm (intermediate particle size range -150/+325 mesh), a height of column, also intermediate (between 1 and 1.5) and several reagent dosage combinations, it was observed the indices that satisfied simultaneously industrial requirements, i.e., a phosphorus grade exceeding 30-33 % and an apatite recovery of more than 60 %. With respect to dissolved air flotation it was noted that it is possible to attain a similar result (P2O5 grade around 29 % and apatite recovery over 60 %) as the one observed in the dispersed air flotation for fine fraction. In this flotation with microbubles, the non floated recirculated pulp flowrate was the variable that more influenced on the apatite flotation performance.